Review: Hannes Heer, Walter Manoschek, Alexander Pollak & Ruth Wodak (2008). The Discursive Construction of History. Remembering the Wehrmacht's War of Annihilation - Dirk Rupnow (Forum: Qualitative Social Research, 2008)
The two Wehrmacht exhibitions (1995/2001) and the debates around them represent an important chapter in the history of how Germany and Austria have dealt with the Nazi past. They strongly challenge the postwar myth of an "untainted Wehrmacht" just as they changed the public perception of the Nazi genocide and its perpetrators. Ruth WODAK and her interdisciplinary team shed light on the Wehrmacht crimes during WWII as well as their subsequent reception and representation. The volume gives an excellent overview of this important part of the history and aftermath of the Holocaust. Its specific layout and structure can also serve as a paradigm for comparable studies. URN: urn:nbn:de:0114-fqs080378